Increasing levels of grain supplementation for intensive-early stocked steers: three-year summary - Cochran, R.C.; Brandt, Robert T., Jr.; Vanzant, E.S.; Clary, E.M.; Owensby, Clenton E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
During the initial 3 years of a 4-year experiment, average daily gain tended to increase in direct proportion to increasing levels of grain sorghum supplementation (2.3, 2.5 and 2.7 lb gain per day for the control and 2 and 4 lb supplement per day, respectively). The amount of grass remaining in the pastures at the end of the growing season (October 1) was greater in each of the 3 years when cattle were supplemented at 4 lb/day. During the 2 years (1989 and 1990) that feedlot performance was monitored, level of supplementation for grazing steers did not influence subsequent feedlot gain or efficiency.
Keywords: Beef; Intensive-early stocking; Supplementation; Grain sorghum; Milo